Roof windows – solutions and limitations. Issue 4 (November 2020) - Tywoniak, J; Stanek, K; Calta, V
Abstract: Paper deals with the roof windows (skylights) from building physics point of view. Based on several introductory analyses an innovative solution of the frame and sash construction was developed in close cooperation with the industrial partner. Resulting parameters correspond to requirements set for passive house level windows (minimized heat transfer, avoided risk of water vapor condensation). The frame and sash consist of effective combination of soft wood and hardened plastics. Glazing unit can be traditional, triple glazed, or double glazed with additional two transparent foils dividing the space into 3 cavities. The analyses also showed that the effect of sloping, and the effect of thermal coupling between window and roof, play a significant role in the overall performance. Thermal transmittance of the roof window, U w, in the best category developed here, is 0.50 W/(m 2 K). When both the effects are included, its real thermal transmittance, U real, is increased to 0.82 W/(m 2 K). Further development ideas and impulses for theoretical studies are mentioned in the final part of the paper.